ANALISIS DETERMINAN KEMISKINAN MULTIDIMENSI DI INDONESIA - Kause, Jeremia; Fithriyah, Fithriyah (Jurnal Riset Ilmu Ekonomi, 2024)
This study aims to identify and analyze the determinants of multidimensional poverty in Indonesia.  This study uses logistic regression and cross-section data sourced from IFLS (Indonesian Family Life Survey) wave 5 in 2014. A total of 37% of households in Indonesia are categorized as poor on a multidimensional basis. Conclusion from this research, variables of educational level of the head of the household, marital status of the head of the household, location of the household, and gender of the head of the household simultaneously have a significant effect on multidimensional poverty. However, the gender variable of the head of the household does not partially have a significant effect on multidimensional poverty. This research can be useful for policymakers in achieving poverty alleviation and for providing new insights related to multidimensional poverty.